Genetic approaches to the analysis of the perception - Gučas, A. (Psichologija, 1968)
The article analyzes the philo-, onto-, and microgenesis process features of perception. Data was recording by daily observation, thought experiments (Kondiljakas), and doing modern laboratory experiments to demonstrate the stages of perception. The article also discusses the hypothesis the mechanisms of perception.